Urban Commons from an Anti-Capitalist Approach - Martínez, Miguel A. (PARTECIPAZIONE E CONFLITTO, 2020)
Many of the contemporary debates on urban commons lack an anti-capitalist approach. In addition, a number of misunderstandings regarding the common wealth, the city, the state, and the public sphere do not help to clarify the meaning of the commons. As a response to these problems, I first devise two useful concepts that stem from Marx's original insights: primary and extended commons. Secondly, I critically examine the institutionalist views on urban commons due to their limitations in advancing anti-capitalist perspectives while also identifying some problems with the Marxist accounts. The different expressions of cooperative housing and squatting serve to illustrate how anti-capitalist urban commons are actually highly developed, despite significant restrictions that are also examined here. Hence, I argue that both the analysis and politics of urban commoning should focus on the joint contentious, cooperative, and democratic practices of the global working class when they deal with essential reproductive work and means of production which are widely independent from state rule and exploitative capitalist relations.